Shifting Loyalties : The Union Occupation of Eastern North Carolina - Browning, Judkin (Book collections on Project MUSE., 2011)
Focusing on the Union occupation of Carteret and Craven Counties in southeastern North Carolina, Browning offers new insights into the effects of war on southerners and the nature of civil-military relations under long-term occupation, especially coastal residents' negotiations with their occupiers and each other as they forged new social, cultural, and political identities.